2008
DOI: 10.1111/j.1365-2117.2008.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Late Carboniferous foreland basin formation and Early Carboniferous stretching in Northwestern Europe: inferences from quantitative subsidence analyses in the Netherlands

Abstract: The large thickness of Upper Carboniferous strata found in the Netherlands suggests that the area was subject to long‐term subsidence. However, the mechanisms responsible for subsidence are not quantified and are poorly known. In the area north of the London Brabant Massif, onshore United Kingdom, subsidence during the Namurian–Westphalian B has been explained by Dinantian rifting, followed by thermal subsidence. In contrast, south and east of the Netherlands, along the southern margin of the Northwest Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Here, the sedimentary basin that covers the onshore part of the Netherlands developed in Devonian and Carboniferous times in response to lithospheric stretching and Late Carboniferous flexural subsidence associated with the Variscan orogenic cycle (Kombrink et al, 2008). The Devonian basin fill is composed of detritic sandstones.…”
Section: Basin Structure and Tectonic Settingmentioning
confidence: 99%
“…Here, the sedimentary basin that covers the onshore part of the Netherlands developed in Devonian and Carboniferous times in response to lithospheric stretching and Late Carboniferous flexural subsidence associated with the Variscan orogenic cycle (Kombrink et al, 2008). The Devonian basin fill is composed of detritic sandstones.…”
Section: Basin Structure and Tectonic Settingmentioning
confidence: 99%
“…Some smaller-scale structures have been recently reported, suggesting the existence of small carbonate buildups. Kombrink et al (2008) reported a small structure on the Texel-IJsselmeer High, interpreted as a carbonate buildup. Van Hulten & Poty (2008) interpreted a similar type of structure in the P10 offshore block.…”
Section: Dinantian Palaeogeography In the Netherlands And The Southermentioning
confidence: 96%
“…The basin lies to the north and east of the London-Brabant Massif (an important high during Carboniferous times) and forms part of the northwest European Carboniferous Basin (Kombrink et al, 2008a). Strata associated with this Variscan foreland basin can be traced along Fm, Epen Formation; GevM, Geverik Member; Zeeland Fm, Zeeland Formation; GoeM, Goeree Member.…”
Section: Geological Settingmentioning
confidence: 99%